STUDI KASUS: ASUHAN KEBIDANAN PASKA PERSALINAN DENGAN RETENSIO URINE - Pepi Hapitria (Jurnal Ilmiah Kebidanan Imelda, 2024)
Postpartum urinary retention is defined as the absence of spontaneous urination or the inability to urinate spontaneously starting 6 hours after vaginal delivery, and the inability to urinate spontaneously 6 hours after catheter removal during delivery with the following actions:caesarean section. This complaint can be caused by hormonal changes, changes in the contractile response of the bladder, innervation trauma that occurs in the bladder, and several other risk factors, namely perineal laceration or episiotomy, delivery with the help of tools, duration of the first stage of labor.>12 hours, duration of second stage of labor>1 hour in multiparas, and birth weight of the baby>3800 grams. The aim of this research is to provide midwifery care to mothers after giving birth who complain of not being able to urinate since 3 days after giving birth. Care is carried out by paying attention to midwifery management steps according to Helen Varney. The research was carried out from 27 March to 09 April 2023 at Gunung Jati Hospital, Cirebon City, using a case study research method and the research subject was Mrs W P1 A0 aged 23 years. Primary and secondary data collection. Primary data was obtained through interviews, observation and physical examination, while secondary data was obtained through documentation and literature studies. The analysis used is descriptive and exploratory through studying data from research subjects. The results of the care were discussed by taking into account similar previous research and a review of relevant literature so that it could be concluded that there was no gap between theory and the care given to Mrs W